The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/s21134386
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Soil Surface Roughness Using Stereo Vision Approach

Abstract: Soil roughness is one of the most challenging issues in the agricultural domain and plays a crucial role in soil quality. The objective of this research was to develop a computerized method based on stereo vision technique to estimate the roughness formed on the agricultural soils. Additionally, soil till quality was investigated by analyzing the height of plow layers. An image dataset was provided in the real conditions of the field. For determining the soil surface roughness, the elevation of clods obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Root Mean Square Error (RMSE) X (Pixel)= 1.07, RMSE Y= 1.65, and RMSE XY= as the Fig. 19[23].HerodowiczMleczak, et al, (2022), this study shows the way of doing a quantitative analysis of the roughness of different soil surfaces. The researchers discovered an intrinsic association that revealed various information regarding the roughness of the soil surface.…”
mentioning
confidence: 63%
“…Root Mean Square Error (RMSE) X (Pixel)= 1.07, RMSE Y= 1.65, and RMSE XY= as the Fig. 19[23].HerodowiczMleczak, et al, (2022), this study shows the way of doing a quantitative analysis of the roughness of different soil surfaces. The researchers discovered an intrinsic association that revealed various information regarding the roughness of the soil surface.…”
mentioning
confidence: 63%
“…. The dataset includes six prairie animals, elephants, zebras, bison, wild horses, giraffes, and hippos, each with about 500 images [48]. Consideration of different time periods, different angles, different distances and occlusions, etc., was achieved by rotating the pictures at different angles, adjusting the contrast, etc.…”
Section: Other Tricksmentioning
confidence: 99%
“…They concluded that the surface soil roughness is more sensitive to the vertical variation of the profile than the horizontal. More recently, Azizi et al [45] developed a computerised approach to estimate surface soil roughness based on the stereo vision technique. They computed the elevation component to reconstruct the 3-D model of the images taken from the field.…”
Section: Introductionmentioning
confidence: 99%